IMAGE BRANDING STRATEGY OF TANDURIA ORGANIC FERTILIZER AND PESTICIDE PRODUCTS - Dewah Hari Sayogo; Nur Magfirah Aestetika2 (Journal of Artificial Intelligence and Digital Economy, 2025)
Objective: This study aims to analyze the branding strategy implemented by Tanduria in building a distinctive brand identity, focusing on aspects such as brand strength, brand uniqueness, and brand favorability. Method: The research employs a qualitative approach with a case study design, utilizing direct observations and in-depth interviews with Tanduria’s founders to explore their branding practices. Results: The findings reveal that Tanduria, as an urban farming platform in Indonesia, successfully promotes its brand through strategies that emphasize ease of use and environmental sustainability, particularly by encouraging the Millennial generation to engage in home-based planting. The branding of Tanduria’s organic fertilizer and pesticide products effectively strengthens its image as a modern, eco-friendly brand that aligns with urban lifestyles. Novelty: This study provides new insights into branding strategies within the urban agriculture industry, demonstrating how environmentally conscious innovation and lifestyle-oriented marketing can enhance brand identity and consumer engagement in the digital era.